Reliability and validity of the Bristol Breastfeeding Assessment Tool in the Turkish population. (February 2018) - Dolgun, Gülümser; İnal, Sevil; Erdim, Leyla; Korkut, Sevda
Abstract: Background: breast milk is a natural source of nourishment, with a high level of bioefficacy that is easily digestible, easy to deliver, providing all the fluids, energy and nutrients that are needed for the optimum growth and development of a newborn. Objective: this research aims to conduct a reliability and validity study of the Bristol Breastfeeding Assessment Tool (BBAT) in the Turkish population. Design: the research was conducted in methodological design. Setting: the Child Health Follow-up Polyclinic of a university hospital in Istanbul. Participants: the participants were 217 breastfed infants and their mothers. Findings: the internal consistency of the Turkish version of Breastfeeding Assessment Tool (Cronbach's alpha = 0.77) and the intraclass correlation level are high (ICC = 0.89). Breastfeeding Assessment Tool displayed a high correlation with LATCH (Latch Audible, Swallowing, Type of Nipple, Comfort of Breast/Nipple, H-Hold/Position) (Pearson r = 0.76; p = 0.000). Conclusions: Breastfeeding Assessment Tool was successfully adapted into Turkish as a reliable and valid breastfeeding assessment tool that can be quickly and easily administered, and it was shown that the instrument could be readily adapted into other languages as well. Implications for Practice: the Turkish version of Breastfeeding Assessment Tool is now available to Turkish midwives and nurses, who will be able to employ an instrument for breastfeeding assessment that has been proven effective. More studies are needed to demonstrate the efficacy of the instrument. Highlights: It is important to evaluate the breastfeeding with a valid and reliable tool. The validity and reliability of BBAT in the Turkish population is high. BBAT is an easy to use scale for Turkish population. Turkish Bristol Breastfeeding Assessment Tool is a useful instrument for investigators researching breastfeeding in Turkish population.